2013
DOI: 10.1002/app.39104
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of porous titanium dioxide sulfonated polystyrene composite microspheres with amphiphilicity

Abstract: Porous particles with amphiphilicity were prepared by a nonpolymeric pore-formation process with the sulfonation of polystyrene microspheres. Nano titanium dioxide (TiO 2 ) particles were then grafted onto the surface via a sol-gel method to finally form the composite particles. The effects of the mass ratio of ethanol (EtOH) to water, temperature, and solubility parameter on the pore-formation process is discussed in detail. The morphology, porous structure, and wetting properties of the particles were studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…It was obviously found that due to the appearance of slightly creased layered graphite, the morphology of microspheres looked like fish-scale pieces. The morphologies and properties of microspheres had been changed before and after modification, which provided direct visual evidence for the presence of graphite and the graphite that was successfully doped into the PS microsphere during polymerization [22,23] . By comparison, the SEM images of quartz sand and resin-coated sand were presented (Figs.…”
Section: Morphologies and Sphericity Of Ps/graphite Composite Microspmentioning
confidence: 98%
“…It was obviously found that due to the appearance of slightly creased layered graphite, the morphology of microspheres looked like fish-scale pieces. The morphologies and properties of microspheres had been changed before and after modification, which provided direct visual evidence for the presence of graphite and the graphite that was successfully doped into the PS microsphere during polymerization [22,23] . By comparison, the SEM images of quartz sand and resin-coated sand were presented (Figs.…”
Section: Morphologies and Sphericity Of Ps/graphite Composite Microspmentioning
confidence: 98%
“…It could be explained that since the density of graphite powder is higher than that of pure PMMA, when they were blended the density of composite particles is between both components, and increased with increasing graphite content. 28 What's more, the density of traditional ULW proppant, such as resin coated and impregnated ground walnut hull and porous ceramic particle coated (not impregnated) by resins, 32,33 were 1.25 and 1.75 g/cm 3 , respectively. Thickening agents, such as guar gum were needed in the fracturing fluid by using conventional high-density hydraulic fracturing proppants, 34 which are contaminative and hard to be degraded.…”
Section: The Densities Of Pmma/graphite Composite Microspheresmentioning
confidence: 99%
“…This provided direct visual evidence that the graphite was successfully doped into the PMMA microsphere during polymerization. 27,28 For comparison, the SEM images of ceramics under different magnification were presented in Figure 5(m,n,o), which showed a rough surface and a bad sphericity to the composite microspheres.…”
Section: Morphology and Properties Of Pmma/graphite Composite Microspmentioning
confidence: 99%